2015
DOI: 10.1155/2015/323409
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity Induced by Intermittent Theta Burst Stimulation in Bilateral Motor Cortices Is Not Altered in Older Adults

Abstract: Numerous studies have reported that plasticity induced in the motor cortex by transcranial magnetic stimulation (TMS) is attenuated in older adults. Those investigations, however, have focused solely on the stimulated hemisphere. Compared to young adults, older adults exhibit more widespread activity across bilateral motor cortices during the performance of unilateral motor tasks, suggesting that the manifestation of plasticity might also be altered. To address this question, twenty young (<35 years old) and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
15
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 53 publications
(70 reference statements)
8
15
1
Order By: Relevance
“…The effect of iTBS on MEP has not been shown to be altered in healthy older adults (Dickins et al, 2015), though Freitas et al (2011) did find advancing age was associated with a reduced effect of cTBS. To our knowledge, no study has explored the relationship between age and TBS effects on TEPs, though several studies have looked at rs-EEG measures in older adults.…”
Section: Discussionmentioning
confidence: 94%
“…The effect of iTBS on MEP has not been shown to be altered in healthy older adults (Dickins et al, 2015), though Freitas et al (2011) did find advancing age was associated with a reduced effect of cTBS. To our knowledge, no study has explored the relationship between age and TBS effects on TEPs, though several studies have looked at rs-EEG measures in older adults.…”
Section: Discussionmentioning
confidence: 94%
“…A couple of studies—including the use of TMS—indicate that cortical excitability and plasticity change with age accompanied by changes in the impact of inhibitory systems (Rogasch et al, 2009 ; Todd et al, 2010 ; Bashir et al, 2014 ). A recent study using iTBS, however, showed no clear age-dependent variations but a high variability of TMS effects in general (Dickins et al, 2015 ). Besides general processes of cellular aging, experience-dependent changes in network wiring strategies are discussed as contributing factors (e.g., Bernard and Seidler, 2012 ).…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have found that TMS measures can be reliably obtained in elderly populations [38], with little adverse side effects [39,40]. Moreover, non-invasive brain stimulation is able to promote plasticity in the older brain [41].…”
Section: Methodsmentioning
confidence: 99%